PEMBUATAN PROGRAM APLIKASI PENJUALAN, PERSEDIAAN, DAN PEMBELIAN PADA OPTIK INDAH - Handy Lesmana; Tony Tony (Jurnal Ilmu Komputer dan Sistem Informasi, 2016)
The development of technology today is a matter that can not be avoided. Use of information technology is proven to improve the competitiveness of enterprises. Not only big companies can apply information technology, but small and medium enterprises can implement it. Information technology has a very important role in facilitating the work of man. In the business world, information technology is one of the priority needs in support of business processes.However, there are still many businesses that do not utilize the optical information technology in data management and still use a lot of paper in running the business. One optical not apply information technology in business processes are Optik Indah which located in Dadap.Some things faced by Optical Indah in conducting its business processes, which are finding customer optometry data is time consuming because still recorded manually, sales invoices can only load one order, and stock glasses are difficult to know.Based on this, the author intends to design a database and create application programs that can support business processes in Optics Indah so it can compete with other optical Dadap in the area. This application is built with the hope of processing data in Optics Indah can be more effective and efficient than the system is done manually before.